ODAM promotes junctional epithelium‐related gene expression via activation of WNT1 signaling pathway in an ameloblast‐like cell line ALC. (16th January 2021) - Song, Danyang; Yang, Sui; Tan, Tao; Wang, Ruijie; Ma, Zeyun; Wang, Yixiang; Wang, Lei
Abstract: Objective: In this study, we investigated the potential and mechanism of odontogenic ameloblast‐associated protein (ODAM) in the promoting junctional epithelium‐related gene expression in an ameloblast‐like cell line ALC. Background: ODAM is expressed in ameloblasts and JE and acts as a component of the inner basal lamina (IBL) and intercellular matrix of JE. ODAM KO mice showed destruction of the integrity of the JE, which detaches from teeth. ODAM was confirmed to regulate the cytoskeleton through the ODAM‐ARHGEF5‐RhoA signaling pathway of the JE. Whether ODAM contributes to the regulation of ameloblast differentiation in JE remains unclear. After the formation of enamel, the ameloblast undergoes a series of morphological changes. Whether ODAM will affect the biological behavior of ameloblasts making them have the characteristics of JE is unclear. Methods: A murine ameloblast‐like cell line, ALC, was used to investigate the effects of ODAM on the JE‐like changes of ALC cells in an epithelium‐induced environment by generating ODAM overexpression and ODAM knockdown cells through a lentivirus transduction approach. The biomarkers of junctional epithelium CK19, SLPI, and ODAM and the potential regulatory gene WNT1 were investigated by real‐time PCR, western blot, immunocytochemistry, immunostaining, luciferase reporter, and rescue assays. Results: ODAM, CK19, and SLPI were significantly upregulated after epithelial induction. Overexpression of ODAM in ALC cells markedly increased CK19 and SLPI expression, while knockdown of ODAM in ALC cells clearly decreased CK19 and SLPI expression. A reporter luciferase assay showed that ODAM activated the WNT signaling pathway, especially through WNT1. Exogenous overexpression of ODAM upregulated WNT1 expression, while knockdown of ODAM reversed this effect. The WNT1 inhibition assay further confirmed the above results and showed that the WNT1 pathway was positively correlated with biomarkers of junctional epithelium CK19 and SLPI expression. Rescue studies showed that knocking down WNT1 in the ODAM‐overexpressing ALC cells decreased the expression of CK19 and SLPI. Immunocytochemistry showed that ODAM colocalized with CK19, SLPI, and WNT1 in the cells. Conclusion: In conclusion, the research work showed that ODAM promotes junctional epithelium‐related gene expression in ALC via the ODAM‐WNT1 axis, which may provide new insight into the function of ODAM and JE formation.